Envelope Protein Gene VP466-a Target for PCR Detection of White Spot Syndrome Virus in Shrimp (Bangladesh Journal of Microbiology, 2016)
White spot syndrome virus (WSSV) is an enveloped and double-stranded DNA virus that belongs to the family Nimaviridae and genus Whispovirus, causing white spot disease (WSD) in shrimp. The virus is highly virulent and leads to 100% mortality within 10 days. Detection of WSSV and segregation of infected brood shrimp, post-larvae and cultured shrimp are currently considered as containment strategies to reduce the spread of WSD. This investigation describes a polymerase chain reaction method to detect WSSV in WSD infected cultured shrimp targeting VP466 gene encoding the large structural protein in virus particle. In silico homology analysis of the primer pair designed in this work clearly identified WSSV VP466 gene sequence with 100% specificity. A total of 16 shrimp samples from 16 farms were selected, where 6 shrimp samples were with characteristics WSD spot and 10 shrimp samples were asymptomatic. Among the 16 shrimp samples, 12 showed PCR positive amplifications for major envelope protein gene VP466. Sequencing of the amplicons followed by homology searching using BLAST further confirmed the presence of WSSV. Phylogenetic analysis of VP466 gene sequences showed its close proximity to the WSSV strain of Indian origin. The present study demonstrates that the envelope protein VP466 gene as a specific target for PCR detection and characterization of WSSV in WSD infected and carrier shrimpsBangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 65-68